Selective Acetogenins and Their Potential as Anticancer Agents - Jacobo-Herrera, Nadia; Pérez-Plasencia, Carlos; Castro-Torres, Víctor Alberto; Martínez-Vázquez, Mariano; González-Esquinca, Alma Rosa; Zentella-Dehesa, Alejandro (Frontiers in Pharmacology, 2019)
The Kingdom Plantae has provided several successful drugs for the treatment of different diseases, including cancer, and continues to be a source of new possible therapeutic molecules. For example, the annonaceous acetogenins (AAs) are secondary metabolites found in the Annonaceae family, which are plants employed in traditional medicine for the treatment of cancer and various other diseases. These polyketides are inhibitors of Complex I in the respiratory chain of tumor cells, a process that is closely related to tumor metabolism, cell death, apoptosis, and autophagy. The goal of this review is to update readers on the role of the AAs as antitumor agents using in vitro and in vivo studies to demonstrate their importance in the area of oncology drug discovery. For this purpose, we performed a literature search in the PubMed scientific database using a range of keywords, including acetogenins and cancer, acetogenins antitumor activity, acetogenins and cytotoxicity, and acetogenins mechanism of action, among others. As a result, we found that the AAs are cytotoxic compounds that can induce apoptosis, cell cycle arrest, and autophagy in vitro, in addition to exhibiting tumor growth inhibition in vivo. The functional group related to their antineoplastic activity is suggested to be the mono or bis tetrahydrofuran ring accompanied by two or more hydroxy groups. The versatility of the AAs bioactivity therefore renders them potential therapeutic agents for cancer treatment. It is therefore apparent that nature is worth further examination to aid in the discovery of more effective, accurate, and less harmful therapies in the fight against cancer.